TINJAUAN LAYOUT PADA INFOGRAFIS WHO “MENGATASI STRES SELAMA WABAH COVID-19” - felicia riherni pratama hutomo; maya putri utami (Universitas Katolik Soegijapranata, Semarang, 2021)
This research was made for us to know about how the usage of principles of layout in the infographic “Mengatasi Stres Selama Wabah Covid-19” are fit with the principles of layout stated by Surianto Rustan. The qualitative descriptive method was used in this research. The data needed was obtained by doing digital research on WHO’s official page, literature study, and sending out surveys for preliminary data. Analysist results said that the infographic “Mengatasi Stres Selama Wabah Covid-19” has fit with the principles of layout by Surianto Rustan which he stated, consisted by four forming points: Sequence, Emphasis, Balance, and Unity. The sequence in this infographic was descending, started right at the top of the page and ended at the bottom of it. Emphasis was shown by the title and the illustrations along with their circles. As in a whole, the balance was symmetrical and the unity of this infographic was shown by the usage of similar or same visual elements through out every page of the infographic.